PERAN PENGASUH MEMBENTUK SIKAP SOSIO EMOSIONAL ANAK (Studi Kasus di Panti Asuhan) - Abdul Syukur (PG-PAUD Trunojoyo, 2015)
Based on 1945 Basic Constitution of the Republic of Indonesia section 34th said "poor and neglected children maintained by the nation". Non-formal education as one of the pathways of education in Indonesia has the same role in educating the children of the nation, one of which is the presence of learning in an orphanage. Education in orphanages are not only how caregivers transferring of knowledge but broader than that relating to the values and skills for children residents. This study used a qualitative approach with a case study strategy. Results of the research are: (1) the caregiver role as substitute parents for children orphanage, (2) in shaping attitudes socio emotional orphanage children caregivers use by the way continues in the sense always give advice in a way that is not too hard, but can be received by children, and (3) the constraints in shaping children's socio emotional attitude is when they adapted to the new environment and adjust the schedule in the orphanage. In conclusion caregiver role in shaping attitudes socio emotional orphanage has been very good.